Aerarium - Ásgeir Jónasson 1989-; Axel Axelsson 1989-; Kristján Oddsson 1989-; Óskar Ómarsson 1985- (2012)
Þetta er lokaskýrsla verkefnisins en hún er ein af 7 skjölum, sem skilað var vegna verkefnisins. Þau er hægt að nálgast á CD-diski á bókasafni Háskólans í Reykjavík. The goal is to design and build a fund portfolio game commissioned by Arion bank. The game will look to fantasy football leagues when it comes to game rules and inspiration. Aerarium will utilize the fund information service that is already implemented within Arion bank. Users will be able to adjust their portfolio on a regular basis and as the funds go up and down in value, so will the user’s capital. Aerarium will utilize real data so that the user’s experience of fund investments is as real as possible, without the risk of losing real money. Within Aerarium there will be a public season that will run for a predefined number of months and private seasons that users in groups can create themselves to compete against each other. Since the world of fund investment does not have seasons the team feels that this feature will help players get into the game at any given time. One of the project’s missions is to teach players how to manage a fund portfolio, introduce asset management to the general public and hopefully make it desirable as an investment strategy. As a bonus, the players will have access to an advisor that posts news online, which will hopefully make people even more involved and help them learn even more than if they were trading in reality. If the project is successful there is a possibility to build a mobile application with notifications for the iPhone and Android platforms. The project’s success criteria is that the aforementioned goals are reached. The development team’s success criteria is that Arion bank decides to put Aerarium into production, advertises it and at least a whole season will commence and finish. Verkefnið var unnið í samvinnu við Arion banka Við þurfum að fá dagsetningu frá Arion banka fyrir það hvenær skýrslan verður aðgengileg öllum.